The Unmet Need for Clinical Guidelines on the Management of Patients with Plaque Psoriasis in Africa and the Middle East - Steinhoff M (Dove Medical Press, 2020)
Martin Steinhoff,1,2 Alfred F Ammoury,3 Haytham Mohamed Ahmed,4 Mohamed Fathy Soliman Gamal,4 Mahira H El Sayed5 1Department of Dermatology and Venereology, and HMC Translational Research Institute, Hamad Medical Corporation, Qatar University, and Weill Cornell Medical College-Qatar, Doha, Qatar; 2Department of Dermatology, Weill Cornell University, New York, NY, USA; 3Dermatology Division, Saint George Hospital University Medical Center, Beirut, Lebanon; 4Pfizer Biopharmaceutical Group, Emerging Markets, Dubai, United Arab Emirates; 5Department of Dermatology and Venereology, Ain Shams University, Cairo, EgyptCorrespondence: Martin SteinhoffDepartment of Dermatology and Venereology, Hamad Medical Corporation, Doha, QatarTel +974 4439 5101Fax +974 4439 4727Email martin_steinhoff@web.dePurpose: Dermatologists practicing in African and Middle Eastern countries face numerous challenges when managing patients with plaque psoriasis, especially those with disease in a difficult-to-treat anatomic area or those who are a pediatric, geriatric, or pregnant patient. The publication of comprehensive, up-to-date, region-specific clinical guidelines may help to address some of these challenges and improve outcomes. We conducted a literature review to identify recent guidelines and other publications describing patients with plaque psoriasis in Africa and the Middle East.Patients and Methods: An online literature search of the PubMed database was conducted to identify publications reporting clinical guidelines and research studies on plaque psoriasis. The search included all articles published from January 2008 to March 2020 inclusive. The titles and abstracts of all search results were screened by a reader to identify those that described patients in Africa or the Middle East.Results: A total of 145 publications were identified by the literature search and screened by a reader. There were 10 publications that described patients in Africa or the Middle East: 4 research articles, 3 reviews, 2 guidelines, and 1 case study. The 2010 guidelines from South Africa made recommendations for treating plaque psoriasis of varying severity, although without specific recommendations for difficult-to-treat anatomic areas or pediatric, geriatric, or pregnant patients. The 2014 guideline on biologics from Saudi Arabia included recommendations for the use of these agents in patients with plaque psoriasis, including difficult-to-treat anatomic areas and pediatric patients (TNF inhibitors only), but provided no recommendations for pregnant or geriatric patients.Conclusion: There is an urgent unmet need for comprehensive clinical guidelines on the management of patients with plaque psoriasis in Africa and the Middle East. Region-specific studies on the epidemiology, burden of disease, and the safety and effectiveness of newer pharmacotherapies are needed to support the development of such guidelines.Keywords: geriatrics, guidelines, pediatrics, pregnancy, psoriasis, unmet needs